Genome sequencing and annotation and phylogenomic analysis of the medicinal mushroom Amauroderma rugosum, a traditional medicinal species in the family Ganodermataceae. (4th March 2021) - Lin, Weiping; Shi, Yanhua; Jia, Guangtao; Sun, Hengyi; Sun, Tongyi; Hou, Dianhai
ABSTRACT: Amauroderma rugosum is one of the traditional Chinese medicinal mushrooms and is used to reduce inflammation, treat diuretic and upset stomach, and prevent cancer. Here, we present a genomic resource of Amauroderma rugosum (ACCC 51706) for further understanding its biology and exploration of the synthesis pathway of bioactive compounds. Genomic DNA was extracted and then subjected to Illumina HiSeq X Ten and PacBio Sequel I sequencing. The final genome is 40.66 Mb in size, with an N50 scaffold size of 36.6 Mb, and encodes 10 181 putative predicted genes. Among them, 6931 genes were functionally annotated. Phylogenomic analysis suggested that A. rugosum and Ganoderma sinense were not clustered together into a group and the latter was grouped with the Polyporaceae. Further, we also identified 377 carbohydrate-active enzymes (CAZymes) and 15 secondary metabolite biosynthetic gene clusters. This is the first genome-scale assembly and annotation for an Amauroderma species. The identification of novel secondary metabolite biosynthetic gene clusters would promote pharmacological research and development of novel bioactive compounds in the future.